Optimizing the Shelling Process of InP/ZnS Quantum Dots Using a Single-Source Shell Precursor: Implications for Lighting and Display Applications - Wang, Zhuang; Wegner, K. David; Stiegler, Lisa; Zhou, Xin; Rezvani, Azita; Odungat, Ahammed Suhail; Apeleo Zubiri, Benjamin; Wu, Mingjian; Spiecker, Erdmann; Walter, Johannes; Resch-Genger, Ute; Segets, Doris (ACS Applied Nano Materials, 2024)
InP/ZnS core/shell quantum dots (QDs), recognized as highly promising heavy-metal-free emitters, are increasingly being utilized in lighting and display applications. Their synthesis in a tubular flow reactor enables production in a highly efficient, scalable, and reproducible manner, particularly when combined with a single-source shell precursor, such as zinc diethyldithiocarbamate (Zn(S2CNEt2)2). However, the photoluminescence quantum yield (PLQY) of QDs synthesized with this route remains significantly lower compared with those synthesized in batch reactors involving multiple steps for the shell growth. Our study identifies the formation of absorbing, yet nonemissive ZnS nanoparticles during the ZnS shell formation process as a main contributing factor to this discrepancy. By varying the shelling conditions, especially the shelling reaction temperature and InP core concentration, we investigated the formation of pure ZnS nanoparticles and their impact on the optical properties, particularly PLQY, of the resultant InP/ZnS QDs through ultraviolet-visible (UV-vis) absorption, steady-state and time-resolved photoluminescence (PL) spectroscopy, scanning transmission electron microscopy (STEM), and analytical ultracentrifugation (AUC) measurements. Our results suggest that process conditions, such as lower shelling temperatures or reduced InP core concentrations (resulting in a lower external surface area), encourage homogeneous nucleation of ZnS. This reduces the availability of shell precursors necessary for effective passivation of the InP core surfaces, ultimately resulting in lower PLQYs. These findings explain the origin of persistently underperforming PLQY of InP/ZnS QDs synthesized from this synthesis route and suggest further optimization strategies to improve their emission for lighting and display applications.
CRIS-Team Scopus Importer:2024-10-25
Keywords: continuous flow synthesis; core/shell; InP/ZnS; quantum dots; single-source precursor